THE INFLUENCE OF TRAINING, EMPLOYEE RELATIONS AND REWARDS ON EMPLOYEE JOB SATISFACTION AT AVICENNA BIREUEN HOSPITAL - Muhammad Iqbal; Sullaida; Em Yusuf Iis; Maisyura (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research aims to determine the influence of training, employee relations and rewards on employee job satisfaction at Avicenna Bireuen Hospital. It can be seen that there are still many complaints from people who often procrastinate because there are some employees who are not yet professional in carrying out their duties and obligations, such as lack of preparation, supervision and control so that many people feel dissatisfied and excessive workload will have a negative impact on employees. The independent variables in this research are training, employee relations and rewards. Meanwhile, the dependent variable is Job Satisfaction. This type of research uses quantitative methods. Data were collected using a questionnaire containing questions and statements by distributing them to the employees concerned at Avicenna Bireuen Hospital. The scoring technique uses a Likert scale. This research was conducted on a sample of 114 employees at Avicenna Hospital Bireuen. The sampling technique uses a census or saturated sample. This research uses multiple linear regression analysis with the SPSS (Statistical Program for Social Science) program. The results of the research show that Training has no positive effect on Job Satisfaction shown by Avicenna Bireuen Hospital employees, Employee Relations has no positive effect on Job Satisfaction shown by Avicenna Bireuen Hospital employees, and Reward has a positive and significant effect on Job Satisfaction shown by Avicenna Hospital employees Bireuen.